ECN Congestion Control Mechanism in IP Networks - Shakya, Subarna; Sainju, Anup (Journal of the Institute of Engineering, 2011)
Explicit Congestion Notification (ECN) is a newer method for congestion control in TCP IP networks. Network Simulator 2 (NS2) software has been used to compare the performance of ECN packet marking to other older and newer congestion control schemes, such as DropTail and Random Early Detection (RED), in both LAN and WAN schemes. During the simulations different parameters including proportion of packet drops, window size variation, queue size, and throughput were measured to evaluate the performance. The overall objective was to independently and comparatively study ECN in a wide range of situations to better understand its advantages and disadvantages. The results of these simulations showed that when all the network prerequisites were met (i.e. all the nodes including being ECN-aware), ECN reduced packet drops and thereby optimized network resource utilization and data throughput. Key Words : Explicit Congestion Notification; Network Simulator; Random Early Detect; DropTail DOI: http://dx.doi.org/10.3126/jie.v8i1-2.5093 Journal of the Institute of Engineering Vol. 8, No. 1&2, 2010/2011 Page : 12-24 Uploaded Date: 19 July, 2011